Sea food by-products valorization for biomedical applications: evaluation of their wound regeneration capabilities in an Ex vivo skin model - Zivelonghi, Giulia; Melotti, Luca; Carolo, Anna; Venerando, Andrea; Roncoroni, Margherita; Martinelli, Giordana; Maccatrozzo, Lisa; Marzorati, Stefania; Sugni, Michela; Patruno, Marco (Frontiers in Veterinary Science, 2024)
IntroductionThe skin is often exposed to harmful stimuli that might compromise its integrity and functionality. After an injury, the skin has a limited capability to restore its complex structure, and in the case of severe skin damage, surgical operations and rapid application of wound dressings are often required to promote optimal wound healing. Nowadays, collagen-based biomaterials are widely used in combination with bioactive molecules able to prevent excessive inflammation and possible infections. In line with a circular economy and blue biotechnology approach, it was recently demonstrated that both collagen and bioactive molecules (i.e., antioxidant compounds) can be sustainably obtained from sea food by-products and effectively used for biomaterial development. Herein, we describe and compare the application of two marine collagen-based wound dressings (CBWDs), produced with materials obtained from sea urchin food waste, for the treatment of skin lesions in a wound healing organ culture (WHOC) model.MethodsThe ex vivo WHOC model was set up starting from rat skin explants and the induced lesions were assigned into three different groups: control (CTRL) group, not treated, marine collagen wound dressing (MCWD) group, and antioxidants-enriched marine collagen wound dressing (A-MCWD) group. After 5 and 10 days, specimens were examined for organ maintenance and assessed for the healing process.ResultsImmunohistochemical results showed that both CBWDs were similarly successful in prolonging skin repair, preserving the epidermal barrier up to 5 days under static culture conditions. Histological and gene expression analysis highlighted that the A-MCWD might support and accelerate skin wound healing by exerting antioxidant activity and counteracting inflammation.DiscussionOverall, these findings underline the potential of sea urchin food waste as a novel resource for the development of functional medical devices for the treatment of skin wounds.